Presentazione delle «Memorie spirituali» di Pietro Favre S.I. - Fiorito, Miguel Angel (La civiltà cattolica, 2021)
Saint Peter Favre (1506-46) was Saint Ignatius of Loyola’s first companion. His Spiritual Memoirs, considered a classic of the spirituality of the Society of Jesus, are presented here. He crisscrossed Europe from 1539 to 1546 to fulfill papal missions, especially in Germany, where he founded the Society of Jesus, and in Belgium and Spain as well. Two personal characteristic traits are highlighted here, namely prayer and his fighting spirit.